Percy and the rabbit - Butterworth, Nick. (London : Collins, 2005)
The Rabbit said,"Look at the mice. They're playing in my house." Can Percy help?
Yollow Band 3.
Keywords: Human- Animals relations -- Fiction; Mice -- Fiction; Rabbit -- Fiction; Snow -- Fiction